Coronavirus disease 2019 in children: Characteristics, antimicrobial treatment, and outcomes - Peng, Hui (J Clin Virol, 2020)
BACKGROUND: At present, coronavirus disease 2019 (COVID-19) has spread in many countries. We conducted this study to help pediatricians understand the conditions of COVID-19 in children. METHODS: We retrospectively summarized the characteristics, treatment and outcomes of pediatric cases in Wuhan Children's Hospital which was the only designated hospital for children with COVID-19 in Hubei Province. A Cox proportional hazards regression analysis was used to evaluate factors associated with clinical outcomes. RESULTS: As of February 29, 75 children had been discharged, of which only one was has severe pneumonia and one was critical cases. Children younger than 2 years were more susceptible to COVID-19. All patients have received interferon-α nebulization, and eight cases including the severe and critical cases were co-administrated ribavirin. Five patients with mild pneumonia were given arbidol. Twenty-three patients were given traditional Chinese medicine (TCM). The average length of stay (LOS) and the time of SARS-CoV-2 clearance were 10.57 and 6.39 days, respectively. None of the factors was associated with LOS or time of SARS-CoV-2 clearance. CONCLUSIONS: The severity of COVID-19 in pediatric cases were milder than adults. The efficacy of the antiviral therapy in children with COVID-19 remains to be evaluated.